Increasing Students’ Listening Skills Through Missing Lyrics In English Songs - Irhamsyah Idris; Sam Hermansyah; Nur Hikmah; Isumarni (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study examined the effectiveness of the Missing Lyrics technique using English songs in improving eighth-grade students’ listening skills, with a specific focus on vocabulary recognition and functional word recognition. It also investigated students’ perceptions of the technique. Adopting a quantitative pre-experimental one-group pretest-posttest design, the research involved 19 purposively selected students from Class VIII A at SMP Negeri 2 Baranti, Sidenreng Rappang Regency, Indonesia. Data were collected through listening comprehension tests (pretest and posttest) and a post-treatment questionnaire, then analyzed using descriptive statistics and a paired-sample t-test in IBM SPSS Statistics. The results revealed a statistically significant improvement in listening performance. The mean score increased substantially from 16.84 (pretest) to 73.95 (posttest), with a significance value of 0.000 (p < 0.05). The correlation between pretest and posttest scores was moderate (r = 0.556). Questionnaire responses indicated that, although students had limited prior exposure to listening activities, they exhibited highly positive perceptions toward the technique. Participants reported increased motivation, greater focus, and higher engagement during lessons, attributing these gains to the enjoyable and authentic nature of English songs. The findings demonstrate that the Missing Lyrics technique is an effective, engaging, and practical strategy for enhancing listening skills in EFL contexts, particularly at the junior secondary level. The approach is recommended for teachers seeking innovative, low-cost methods to promote active listening and vocabulary development through authentic materials.